THE IMPACT OF THE INCLUSION OF MAHOGANY (Swietenia macrophylla) IN CITES APPENDIX II: ANALYSIS OF TRADE IN PERU AND ITS GLOBAL COMPARISON - GUTIERREZ PERALTA, HAROL (2025)
Mahogany (Swietenia macrophylla) is a timber species that has historically been in high international demand. It was listed in Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) in 2002. This study examines the impact of this measure on the trade of mahogany in Peru and compares it with global trends. Export volume data from 1995 to 2023 were utilised, analysing changes before and after the entry into force of Appendix II. The effects of regulatory measures were assessed using Mann–Whitney U tests and LOESS smoothing models. Furthermore, available population data were used to model the population through a Lefkovitch matrix. The results indicate that Peruvian exports (U = 93, p = 0.212) did not exhibit a significant change in trade volume; however, at the global level (U = 145, p = 0.002), statistically significant differences in export volume were observed before and after its inclusion in CITES. The population model (Lefkovitch) yielded a population growth rate of λ = 1.006, suggesting a stable condition under the current harvesting regime.